泰国大学生通用就业能力提升路径研究 - Chantharaphon, Chittima; Lijun, Jia (Confucius Institute Universitas Sebelas Maret, 2024)
Todays, the number of graduates has rapidly increased; hence, this situation will affect the difficulty of applying jobs and employment of graduates. Therefore, improving employability skills of the graduates will be a seriously concerned issue of many higher education institutions. Due to undergraduates’ perspective on general employability skills, there are specialized differences of disciplines and qualifications of each field. The general employability skills are standard abilities and qualities of Thai undergraduates which are used to consider for employment. Moreover, basic employability abilities skills, professional abilities, non-technical skills and transferable skills are also included for seeking and gaining employment. This article is conducted according to the basic principles of Thailand Qualification Framework (TQF). This paper studies definitions of general employability skills including explore and understand the current situations of employability skills of Thai undergraduates. This article used in-depth interviews which interviewed three relevant groups consisting of lecturers, organizations, and graduates. The factors influencing employability include: social factors, individual factors, family factors, and higher education factors. Therefore, the results of this article can be used to develop the curriculum of higher education institutions, especially, in general employability skill perspective to be more efficient. The recommendations of this article are given for new graduates in Thailand.